2016
DOI: 10.1038/nrneurol.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive plasticity in tinnitus — triggers, mechanisms and treatment

Abstract: Tinnitus is a phantom auditory sensation that reduces quality of life for millions worldwide and for which there is no medical cure. Most cases are associated with hearing loss caused by the aging process or noise exposure. Because exposure to loud recreational sound is common among youthful populations, young persons are at increasing risk. Head or neck injuries can also trigger the development of tinnitus, as altered somatosensory input can affect auditory pathways and lead to tinnitus or modulate its intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
314
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(329 citation statements)
references
References 166 publications
(206 reference statements)
7
314
0
8
Order By: Relevance
“…This case demonstrates that tinnitus modulation can be found even when no somatic disorder is present; in fact, somatic modulation of tinnitus is a widespread condition that can be present with or without underlying somatic disorders 31,40 . Furthermore, as previously discussed, several authors reported a large capability of somatic tinnitus modulation in multiple patient series ranging between 65.3% and 83.3% 32,35,[41][42][43]45,47,61,65 . In this patient, the negative history for self-reported somatic disorder suggests caution while taking into account a somatic origin for his tinnitus.…”
Section: Comments On This Casesupporting
confidence: 53%
See 2 more Smart Citations
“…This case demonstrates that tinnitus modulation can be found even when no somatic disorder is present; in fact, somatic modulation of tinnitus is a widespread condition that can be present with or without underlying somatic disorders 31,40 . Furthermore, as previously discussed, several authors reported a large capability of somatic tinnitus modulation in multiple patient series ranging between 65.3% and 83.3% 32,35,[41][42][43]45,47,61,65 . In this patient, the negative history for self-reported somatic disorder suggests caution while taking into account a somatic origin for his tinnitus.…”
Section: Comments On This Casesupporting
confidence: 53%
“…Levine 42 described this phenomenon as a "fundamental characteristic of tinnitus", like its auditory and affective attributes. Somatic modulation has been reported in approximately two-thirds of tinnitus patients 35,43 ; other studies revealed tinnitus modulation in 85% 45 TMJ is the most common affected region in patients with somatic tinnitus. Rubinstein studied 102 individuals with tinnitus reporting that about one-third of the patients had influence on tinnitus by mandibular movements and/ or pressure applied to the temporomandibular joint [63][64][65] and found that subjects with tinnitus had a significantly higher prevalence of cranio-mandibular disorders.…”
Section: Considerations On Somatic Modulation Of Tinnitusmentioning
confidence: 95%
See 1 more Smart Citation
“…Numerous types of treatment modalities, such as oral medication, retraining therapy, or transtympanic laser therapy, have been attempted [3] . However, because of the unclear etiology of tinnitus in most cases, clinicians often fail to constitute a proper algorithm that can effectively treat it.…”
Section: Introductionmentioning
confidence: 99%
“…Data from animal studies indicates the relay of afferent somatosensory information by the trigeminal and dorsal root ganglia; somatosensory input causes changes in the firing rate and synchrony in dorsal cochlear nucleus neurons that may be at the base of somatic tinnitus. 16,17 The modulation of tinnitus by somatic movements is widely diffused among acute and chronic tinnitus sufferers and has been reported to involve one to two-thirds of them with different patient series ranging between 65% and 83%. [18][19][20][21][22] Several authors have developed sets of maneuvers to modulate tinnitus; a detailed description of these maneuvers has been published by Won in 2013 comparing the prevalence and characteristics of somatic modulation found in six previous studies.…”
Section: Introductionmentioning
confidence: 99%